Sulla relazione tra classe ed egemonia - Balsa, Juan Javier (2022)
This article examines the complexity of the relationship between social classes and hegemony. First, it analyzes how the universalist component and rhetorical discourse tend not to make this relationship explicit.Secondly, it reflects on the need to recover the concept of "class interest" and maintain a critical-speculative perspective to establish this relationship. And, finally, it addresses the complexity of the construction-recognition of these interests in the disputes for hegemony, with the essential mediation of different types of intellectuals.